Comparative Assessment of the Safety between Pazopanib and Sunitinib for Metastatic Renal Cell Carcinoma - Eka Yudha Rahman; Choirin Nur; Deddy Rasyidan Yulizar (Jurnal Kedokteran Brawijaya, 2022)
Renal cell carcinoma (RCC) is the most common kidney lesion with approximately 90% of all kidney malignancies and 30% of people with RCC have developed metastasis at the time of diagnosis. Based on European Association of Urology (EAU) guideline, therapy for metastatic RCC (mRCC) patient who cannot tolerate immune checkpoint inhibitor is pazopanib or sunitinib. However, these drugs cause several uncomfortable side effects for the patient. Therefore, this meta-analysis was made, based on the available evidence base, to compare the safety of pazopanib and sunitinib as the treatment of mRCC. Systematic reviews were made in accordance with the PRISMA guideline requirements, a literature review was conducted in January 2022 used PubMed, ScienceDirect, Cochrane Library, publishing year of at least 10 years with an adult population. And the data is analyzed using RevMan V.5.4. In total 1.665 participants, there were 431 patients taking pazopanib and 1.234 patients taking sunitinib from 8 studies. The result shows that sunitinib has more frequent result of side effects than pazopanib in several occasion like hand-foot syndrome, nausea/vomiting, skin rash, stomatitis & mucosal inflammation, leucopenia and thrombocytopenia. Meanwhile, there are no significant differences between pazopanib and sunitinib in causing other side effect such as fatigue, diarrhea, hypertension, anemia, and increased liver enzymes. The conclusion is that pazopanib is better and has less frequent side effects than sunitinib.